Um oásis de horror: o grotesco em Romance negro e outras histórias, de Rubem Fonseca - Luís Otávio Hott (2015)
This study is devoted to the analysis of narrative strategies that enable the representation of different aspects of the grotesque in 'Romance negro e outras histórias', written by Rubem Fonseca, proposing to account for the grotesque as a discursive genre, literary aesthetics, attitude and cultural practice, operating through two main routes: the grotesque as the predominant aesthetic representation in contemporary society and the grotesque as a form of transgression of social codes enforced in modern capitalist societies.